Variants with a low allele frequency detected in genomic DNA affect the accuracy of mutation detection in cell‐free DNA by next‐generation sequencing. Issue 5 (27th November 2017) - Wang, Jacqueline F.; Pu, Xingxiang; Zhang, Xiaoshan; Chen, Ken; Xi, Yuanxin; Wang, Jing; Mao, Xizeng; Zhang, Jianhua; Heymach, John V.; Antonoff, Mara B.; Hofstetter, Wayne L.; Mehran, Reza J.; et al.
Abstract : BACKGROUND: Next‐generation sequencing of cell‐free DNA (cfDNA) has been shown to be a useful noninvasive test for detecting mutations in solid tumors. METHODS: Targeted gene sequencing was performed with a panel of 263 cancer‐related genes for cfDNA and genomic DNA of peripheral blood mononuclear cells (PBMCs) obtained from presurgical specimens of 6 lung cancer patients, and mutation calls in these samples were compared with those of primary tumors and corresponding patient‐derived xenografts (PDXs). RESULTS: Approximately 67% of the mutations detected in the tumor samples (primary tumors and/or PDXs) were also detected in genomic DNA from PBMCs as background mutations. These background mutations consisted of germline polymorphisms and a group of mutations with low allele frequencies, mostly <10%. These variants with a low allele frequency were repeatedly detected in all types of samples from the same patients and at similarly low allele frequency levels in PBMCs from different patients; this indicated that their detection might be derived from common causes, such as homologous sequences in the human genome. Allele frequencies of mutations detected in both primary tumors and cfDNA showed 2 patterns: 1) low allele frequencies (approximately 1%‐10%) in cfDNA but high allele frequencies (usually >10% or >3‐fold increase) in primary tumors and further enrichment in PDXs and 2) similar allele frequencies across samples. CONCLUSIONS: Because only a small fraction of total cfDNA might be derived from tumor cells, only mutations with the first allele frequency pattern may be regarded as tumor‐specific mutations in cfDNA. Effective filtering of background mutations will be required to improve the accuracy of mutation calls in cfDNA. Cancer 2018;124:1061‐9 . © 2017 American Cancer Society . Abstract : Some variants with a low allele frequency have been repeatedly detected in all types of samples from the same patients and at similarly low allele frequency levels in peripheral blood mononuclear cells from different patients, and they affect the accuracy of mutation detection in cell‐free DNA. Effective filtering of these background mutations will be required to improve the accuracy of mutation calls in cell‐free DNA.